Stimulation of exosome release by extracellular DNA is conserved across multiple cell types - Iliev, Dimitar Borisov; Strandskog, Guro; Nepal, Arpita; Aspar, Augusta; Olsen, Randi; Jørgensen, Jorunn B; Wolfson, Deanna; Ahluwalia, Balpreet Singh; Handzhiyski, Jordan; Mironova, Roumyana (The FEBS Journal, 2018)
This is the submitted manuscript version of the following article Iliev, D., Strandskog, G., Nepal, A., Aspar, A., Olsen, R., Jørgensen, J., . Mironova, R. (2018). Stimulation of exosome release by extracellular DNA is conserved across multiple cell types. The FEBS Journal , 285(16), 3114-3133. https://doi.org/10.1111/febs.14601. Published version available at https://doi.org/10.1111/febs.14601 . Exosomes are distinguished from other types of extracellular vesicles by their small and relatively uniform size (30-100 nm) and their composition which reflects their endo-lysosomal origin. Involvement of these extracellular organelles in intercellular communication and their implication in pathological conditions has fuelled intensive research on mammalian exosomes; however, currently, very little is known about exosomes in lower vertebrates. Here we show that, in primary cultures of head kidney leukocytes from Atlantic salmon ( Salmo salar ), phosphorothioate CpG oligodeoxynucleotides induce secretion of vesicles with characteristics very similar to these of mammalian exosomes. Further experiments revealed that the oligonucleotide-induced exosome secretion did not depend on the CpG motifs but it relied on the phosphorothioate modification of the internucleotide linkage. Exosome secretion was also induced by genomic bacterial and eukaryotic DNA in toll-like receptor 9-negative piscine and human cell lines demonstrating that this is a phylogenetically conserved phenomenon which does not depend on activation of immune signaling pathways. In addition to exosomes, stimulation with phosphorothioate oligonucleotides and genomic DNA induced secretion of LC3B-II, an autophagosome marker, which was associated with vesicles of diverse size and morphology, possibly derived from autophagosome-related intracellular compartments. Overall, this work reveals a previously unrecognized biological activity of phosphorothioate ODNs and genomic DNA – their capacity to induce secretion of exosomes and other types of extracellular ...